Slip of the Tongue and Gender Relation in Advance Debate Community - Mochammad Yusril Ihza Maldini; Rohmani Nur Indah (Universitas Pendidikan Mandalika, 2020)
This study discusses the slip of the tongue found in male and female debaters of Advance Debate Community (ADC). This particular topic is chosen with the assumption that gender difference can influence slip of the tongue. It aims at describing how the slip of the tongue produced by male and female debaters on ADC debate performance. In addition, it deciphers the factors causing the slips of tongue. To get the intended results, this study used descriptive analysis to explain the existing data. The ADC debate record was converted to text manually. Then, the result was identified into the utterances containing slip of tongue. The researchers classified data types based on the slip of tongue model according to Caroll (1986). There are eight types of slip of tongue presented, namely: anticipation, perseveration, reversal/exchange, blend, misderivation, substitution, addition and deletion. The findings show that the male debaters produce more slip of tongue by displaying thirteen slip of tongue with five different types, namely: anticipation, misderivation, substitution, addition, and deletion. While female debaters display fewer slip of tongue, that is nine slip of tongue but more varied with six different types, namely: anticipation, blend, misderivation, substitution, addition and deletion.